Insulin resistance during androgen deprivation therapy in men with prostate cancer - Basaria, Shehzad; Taplin, Mary‐Ellen; McDonnell, Marie; Simonson, Donald C.; Lin, Alexander P.; Dufour, Alyssa B.; Habtemariam, Daniel; Nguyen, Paul L.; Ravi, Praful; Kibel, Adam S.; Sweeney, Christopher J.; D’Amico, Anthony V.; et al. (Cancer, 2024)
Background Androgen deprivation therapy (ADT) in prostate cancer (PCa) has been associated with development of insulin resistance. However, the predominant site of insulin resistance remains unclear. Methods The ADT & Metabolism Study was a single‐center, 24‐week, prospective observational study that enrolled ADT‐naive men without diabetes who were starting ADT for at least 24 weeks (ADT group, n = 42). The control group comprised men without diabetes with prior history of PCa who were in remission after prostatectomy (non‐ADT group, n = 23). Prevalent diabetes mellitus was excluded in both groups using all three laboratory criteria defined in the American Diabetes Association guidelines. All participants were eugonadal at enrollment. The primary outcome was to elucidate the predominant site of insulin resistance (liver or skeletal muscle). Secondary outcomes included assessments of body composition, and hepatic and intramyocellular fat. Outcomes were assessed at baseline, 12, and 24 weeks. Results At 24 weeks, there was no change in hepatic (1.2; 95% confidence interval [CI], −2.10 to 4.43; p = .47) or skeletal muscle (−3.2; 95% CI, −7.07 to 0.66; p = .10) insulin resistance in the ADT group. No increase in hepatic or intramyocellular fat deposition or worsening of glucose was seen. These changes were mirrored by those observed in the non‐ADT group. Men undergoing ADT gained 3.7 kg of fat mass. Conclusions In men with PCa and no diabetes, 24 weeks of ADT did not change insulin resistance despite adverse body composition changes. These findings should be reassuring for treating physicians and for patients who are being considered for short‐term ADT. In this prospective study of hormone‐naive men who were eugonadal and did not have diabetes, 24 weeks of androgen deprivation therapy (ADT) for prostate cancer (PCa) was not associated with worsening of hepatic or skeletal muscle insulin resistance despite a substantial increase in fat mass. These findings have relevance for both physicians and patients when determining treatment for PCa and suggest that a short course of ADT may not worsen metabolic risk in patients without pre‐existing diabetes.